TBBPA and its alternative TCBPA induced ROS-dependent mitochondria-mediated apoptosis in the liver of Rana nigromaculata. (15th March 2022) - Jia, Xiuying; Yan, Ruopeng; Lin, Huikang; Liu, Zhiquan; Shen, Lilai; Yang, Hongmei; Wu, Haoying; Shan, Xiaodong; Zhang, Hangjun
Abstract: Tetrabromobisphenol A (TBBPA), which is the most widely employed brominated flame retardant, and its alternative tetrachlorobisphenol A (TCBPA) are widely distributed in aquatic environments. In the present study, the hepatotoxicity induced by TBBPA and TCBPA was investigated in Rana nigromaculata, and the potential mechanisms were investigated with a particular focus on ROS (reactive oxygen species) -dependent mitochondria-mediated apoptosis. Healthy adult frogs were exposed to 0, 0.001, 0.01, 0.1, and 1 mg/L waterborne TBBPA and TCBPA for 14 days. The results showed that liver weight was significantly increased by 51.52%–98.99% in the 0.01, 0.1, and 1 mg/L TBBPA and TCBPA groups relative to the control. Histological examination revealed that the structure of the liver, to some extent, was influenced by TBBPA and TCBPA with nuclear shrinkage and mitochondrial swelling. Meanwhile, TBBPA and TCBPA have significantly increased the alanine transaminase level in serum and the content of ROS, while inhibiting the activity of superoxide dismutase in the liver. In addition, DNA fragments were observed in the TBBPA and TCBPA groups relative to the control. Expression of Cytochrome C was significantly increased by 1.13-, 1.38-, 1.60-, and 2.46-fold in 0.001, 0.01, 0.1, and 1 mg/L TBBPA, and by 1.26-, 1.51-, 2.14-, and 2.98- fold in 0.001, 0.01, 0.1, and 1 mg/L TCBPA, respectively, which indicated that TCBPA may be more toxic than TBBPA. Similarly, the ratio of Bax/Bcl-2 was increased in a dose-dependent manner. These results indicated that apoptosis in the ROS-dependent mitochondrial pathway mediates hepatotoxicity caused by TBBPA and TCBPA. The present study will facilitate an understanding of the toxicity mechanism of flame retardants. Graphical abstract: Image 1 Highlights: TCBPA is similar to or even more toxic than TBBPA. TBBPA and TCBPA caused liver damage in R. nigromaculata. TBBPA and TCBPA induced oxidative stress and caused hepatocyte apoptosis in R. nigromaculata.